Strategic plan for Fútbol Más Perú - Padilla, Gerardo (2015)
The purpose if this work is to elaborate a strategic plan for the period 2015-2019 for Fútbol Más Perú, a non-profit association that started operations in Peru in February 2015. The information used for this document has been provided by the organization and by the authors’ own research. This plan has followed the model proposed by Dr. D’Alessio (2013). After reviewing the organization’s general situation and background, a new vision and mission are given; these consider both the theory and the organization’s purpose of existence. Afterwards, the external environment is analyzed to discover the players, opportunities and threats that Fútbol Más Perú will have to face. This analysis is combined with an internal evaluation of the organization, in order to find out what its main strong and weak points are, and how these cope with the environment. This analysis supports the formulation of four long-term objectives -and the respective short-term objectives- that the organization has to accomplish to see its vision fulfilled. These objectives consider the internal and external analysis and the organization’s vision and mission. Six strategies were chosen to enable the achievement of the objectives. The implementation of the strategies will be managed by controlling the achievement of the short-term objectives utilizing the Balanced Scorecard tool. Results of this work show that Fútbol Más Perú needs to increase its brand awareness to successfully attract private sponsors for its projects. Despite of having limited human resources it is possible to exploit resources not used currently, such as social media, to become more popular in the local environment.